The effect of problem-based learning on students' critical thinking skills in school - Siradjuddin, Suharti; Hasanah, Uswati; Handayani (Creative Smart Visionary, 2025)
This study aims to explore the influence of Problem-Based Learning (PBL) on improving students' critical thinking skills in schools. PBL is a learning method that prioritizes solving real-world problems as a means to develop critical thinking skills. This study used a pseudo-experimental design with two groups, namely the experimental group that followed problem-based learning and the control group that followed conventional learning. Data was collected through pre-tests and post-tests to measure changes in critical thinking skills, as well as questionnaires to explore students' perceptions of the learning methods applied. The results showed that the experimental group experienced a significant improvement in critical thinking skills compared to the control group. The implementation of PBL was also responded positively by students, who felt more engaged in learning and more motivated. These findings indicate that PBL is effective in improving students' critical thinking skills, with supporting factors such as student engagement and teacher readiness playing an important role. The implication of this study is the importance of teacher training and the provision of adequate resources to optimize the implementation of PBL in schools in Indonesia.